SOLIPSISME DAN FENOMENALISME: DUA KUTUB EKSTRIM KANTIAN YANG MENGOYAK SPIRITUALITAS - Heriyanto, Husain (Kanz Philosophia A Journal for Islamic Philosophy and Mysticism, 2013)
Solipsism, which is set up by a very infl uential modern philosopher Immanuel Kant, constitutes one main characteristic of modern philosophy and thought. In the realm on metaphysics, it has brought down the meaning of reality. In epistemological perspective, it has caused modern man to live and think in an isolated mental world that is alienated from objective reality. In the levels of ethics and psychology, it paves the way for fl ourishing any kind of self-centered standpoint and attitude such as individualism, egoism, racism, and anthropocentrism in the context of human and universe relation. We however fi nd another kind of solipsism in the context of theology and religion (focused on Muslim community). Neo-Salafi Wahhabi puritanism that appears to claim its doctrine as a purifi ed version of Islamic teachings and tradition is essentially an elimination and alienation of Islamic Ummah from transcendent reality, universe, history, humanity, and civilization. Similar to Kantian ontological assumption, Wahhabi insists to believe in transcendent reality with denial of the gates and ways of understanding the reality as well as with removal the keys of revealing reality. Both Kant and Wahhabi reject the capability of human reason to grasp and understand the transcendent reality.